Effectiveness of crystallitic carbon from coal as milling aid and for hydrogen storage during milling with magnesium - Zhou, Shixue; Chen, Haipeng; Ding, Chao; Niu, Haili; Zhang, Tonghuan; Wang, Naifei; Zhang, Qianqian; Liu, Di; Han, Shuna; Yu, Hongguan (Fuel (Guildford), 2013)
► Carbon from coal acted as dispersant, lubricant and milling media for Mg milling. ► The Mg easily hydrided into β-MgH2 and γ-MgH2 during milling under hydrogen. ► Nanocomposites with hydrogen capacity of 6.67wt.% were prepared by 3h of milling. ► CH dangling bonds made some contribution to hydrogen capacity of the composites. This paper is concerned with the functions of crystallitic carbon, prepared from anthracite coal by demineralization and carbonization, for making Mg-based nanocomposites for hydrogen storage by reactive milling under hydrogen atmosphere. The TEM and XRD analysis show that in the presence of 30wt.% of crystallitic carbon, the Mg easily hydrided into β-MgH2 of particle size 20–60nm and crystal grain size 29.7nm and a small amount of γ-MgH2 after 3h of milling under 1MPa H2. The hydrogen content of the composites is up to 5.81wt.% determined by water displacement method, and its dehydrogenation peak temperature is 344.2°C by DSC analysis. The enthalpy and entropy changes of the hydrogen desorption reaction are 42.7kJ/mol and 80.7J/molK, respectively, calculated by the van’t Hoff equation from the p–C–T data in 300–380°C. With the extension of milling time, more γ-MgH2 yielded, and the endothermic peak of γ-MgH2 separated from that of β-MgH2. The CH dangling bonds in the hydrogenated carbon were determined by FT-IR analysis. The dehydrogenation temperature of the materials decreased with the addition of Co, Ni, Fe and Al.